2016
DOI: 10.1108/jpbm-02-2016-1101
|View full text |Cite
|
Sign up to set email alerts
|

Quantity consumer goods pricing: has yesterday’s surcharge become today’s discount?

Abstract: Purpose This study aims to extend by way of replication an earlier study, “Blind man’s bluff: The ethics of quantity surcharges” (Gupta and Rominger, 1996) by testing several hypotheses regarding changes in the surcharging phenomenon that may have occurred over time. Design/methodology/approach The original study was constructed from data collected 20 years ago. This study went beyond a mere replication. A key difference between this study and the original study was in the method of data collection. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Bulk discounting is measured as the price per volume price difference between the largest and smallest sized items offered by the brand, capturing how much a consumer saves per ounce when purchasing the largest item available versus the smallest item. Bulk discounting has become a common market practice and is generally expected to improve sales performance (Dunphy, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Bulk discounting is measured as the price per volume price difference between the largest and smallest sized items offered by the brand, capturing how much a consumer saves per ounce when purchasing the largest item available versus the smallest item. Bulk discounting has become a common market practice and is generally expected to improve sales performance (Dunphy, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Brands understand the importance of creating a strong customer demand. When Walmart decided to pull Hefty and Glad food bags from its shelves, selling just Ziploc and its own Great Value brand, Hefty and Glad stood to lose because the retail giant accounted for a third of its sales (Dunphy, 2016). Consumers were not satisfied and complained about their loss.…”
Section: Critical Success Factors For Private Labelsmentioning
confidence: 99%
“…They switched and started shopping from other stores. Walmart understood the consumer reactions and put the brands back on the shelves (Dunphy, 2016).…”
Section: Critical Success Factors For Private Labelsmentioning
confidence: 99%
“…QD is considered the most widely used pricing tactic in the marketplace (Binkley and Bejnarowicz, 2003;Gupta and Rominger, 1996;Widrick, 1985). However, numerous field studies have confirmed incidences of QS in various grocery products and stores (Widrick, 1979a;Dunphy, 2016). Figure 1 shows real illustrations of QD and QS offered by the same grocery store in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Although QS may occur unintentionally through retailers' common price-setting practices, consumers who adopt the strategy may feel exploited when they find out that they purchased a surcharged size (Sprott et al, 2003;Widrick, 1979b). Similarly, Dunphy (2016) stated that QS might be seen as unfair and disrespectful to consumers who assume that they can save money by purchasing larger packages. Hence, it is vital to incorporate brand-size pricing into marketing decision-making (Sprott et al, 2003).…”
Section: Introductionmentioning
confidence: 99%